RF15 Participants' perspectives and preferences on clinical trial result dissemination: the TRUST thyroid trial experience. (September 2018) - Racine, E; Hurley, C; Cheung, A; Sinnott, C; Matvienko-Sikar, K; Smithson, WH; Kearney, PM
Abstract : Background: While there is an increasing consensus that clinical trial results should be shared with trial participants, there is a lack of evidence on the most appropriate methods. The aim of this study is to use a patient and public involvement (PPI) approach to identify, develop and evaluate a patient-preferred method of receiving results of the Thyroid Hormone Replacement for Subclinical Hypo-Thyroidism Trial (TRUST). Methods: This is a mixed methods study with three consecutive phases. Phase 1 iteratively developed a patient-preferred result method using semi-structured focus groups and a consensus-orientated-decision model to achieve consensus, a PPI group to refine the method and adult literacy review for plain English assessment. Phase 2 was a single-blind parallel group trial. Irish TRUST participants were randomised to the intervention (patient-preferred method) and control group (standard dissemination method as developed by lead study site in Glasgow, Scotland). Phase 3 used a patient understanding questionnaire to compare patient understanding of results between the two dissemination methods. Results: Patients want to receive results of clinical trials, with qualitative findings of perspectives and preferences indicating three key themes including 'acknowledgement of individual contribution', 'contributing for a collective benefit' and 'receiving accessible and easy to understand results'. Building on these findings, a patient-preferred method of receiving results was developed by researchers, trial participants and adult literacy experts. One hundred and one TRUST participants were then randomised to receive the patient-preferred result method or the standard dissemination method. The questionnaire response rate was 74% for the intervention group and 62% for the control group. There were no differences in patient understanding between the two dissemination methods. Conclusion: Patient and Public Involvement (PPI) is advocated for every step of the trial process. We have demonstrated that it is feasible to do this with regard to the dissemination of results. The study identified and developed a patient-preferred method of receiving clinical trial results for older adults over 65 years. Although, in this study PPI did not influence patients' final understanding of results, it provides a record of the process of conducting PPI within the clinical trial setting.